The impact of different heat treatments on the surface characteristics, residual stresses, and tensile strength of maraging steel 1.2709 samples produced by LPBF - V. Raghuraman; T. Sampath Kumar (Results in Engineering)
Post-processing and heat treatment techniques effectively reduce residual stress in metal parts produced through additive manufacturing (AM), thereby enhancing mechanical properties and extending their service life. The present study investigates the impact of aging, double aging, and solutioning the heat treatments on surface characteristics, residual stresses, and tensile behaviour of laser powder bed fusion (LPBF) maraging steel, which has critical applications in aerospace and defence. Surface analysis of the steel parts scans the tracks in the as-built samples, with aging that causes deformations. Aging treatment proves to be more effective than double aging and solutioning treatments. Aged treatment (AT) samples have a higher surface roughness of 4.65 µm and shows greater tensile strength of 1510 MPa and lower residual stress of -188 MPa compared to other heat-treated (HT) and as-built samples. It forms the precipitates that prevent dislocation movements, and the conversion of tensile into compressive residual stresses. The LPBF process plays a critical role due to its rapid cooling capability, which results in elevated residual stresses. Controlled thermal and mechanical processes reduce internal stresses, and stabilize the components. This research explores the influence of heat treatment on LPBF maraging steel. Optimized heat treatments can be developed to improve the mechanical properties and surface characteristics of the components.